The Raspberry Rules - McCombie, Karen (Scholastic Ltd, 2010)
Rowan Love is thirteen and full of good intentions. so why does life keep going so wrong? Her teachers think she's dippy and diorganized, her best friend has new mates, and nobody appreciates her unique fashion sense. Maybe keeping a diary will help? Wander through Rowan's funny and fabulous journal and find out all about hero worship, fairy lights, guardian angels, and making hair accessories out of sweet wrappers!
Keywords: Juvenile literature-Fiction